The Roots of Curriculum Integration in Modern Philosophy and Educational Thought - Villanueva, Juliet Aleta R. (Alipato, A Journal of Basic Education; Vol 3 No 2 (2008), 2025)
A variety of views and practices of curriculum integration have grown over the years as documented in research abroad.  However, the need to look into its philosophical foundations is necessary if we are to make sense of its practice and its implications in the local context. This study is based on a historical research which examined the roots of curriculum integration in the works of Rousseau, Pestalozzi, Herbart, Kilpatrick and Dewey in modern history. This paper presents findings from this historical research which show that curriculum integration originated from J.F. Herbart who grounded his work on the ideas of Pestalozzi. Curriculum integration reappeared as core curriculum in the 1930’s as experimentalism and progressivism have taken root to push forth curriculum reform movements in the United States. The paper points to the fact that the Philippines does not have a history of progressive movement to fuel integrated  curriculum and become an accepted and effective practice in the local setting. However, its feasibility and application in the local setting can  be further investigated through future studies about local progressive schools.